2023
DOI: 10.3390/antiox12030603
|View full text |Cite
|
Sign up to set email alerts
|

Role of 3-Mercaptopyruvate Sulfurtransferase (3-MST) in Physiology and Disease

Abstract: 3-mercaptopyruvate sulfurtransferase (3-MST) plays the important role of producing hydrogen sulfide. Conserved from bacteria to Mammalia, this enzyme is localized in mitochondria as well as the cytoplasm. 3-MST mediates the reaction of 3-mercaptopyruvate with dihydrolipoic acid and thioredoxin to produce hydrogen sulfide. Hydrogen sulfide is also produced through cystathionine beta-synthase and cystathionine gamma-lyase, along with 3-MST, and is known to alleviate a variety of illnesses such as cancer, heart d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 126 publications
0
6
0
Order By: Relevance
“…Our results showed that only 3MST expression was not boosted by taurine supplementation. Unlike other H 2 S-producing enzymes, 3MST is located in the mitochondria and catalyzes the production of H 2 S with 3-mercaptopyruvate as the donor of sulfur [31]. Further studies are required to investigate whether taurine differentially regulates H 2 S-producing enzyme expression for such reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that only 3MST expression was not boosted by taurine supplementation. Unlike other H 2 S-producing enzymes, 3MST is located in the mitochondria and catalyzes the production of H 2 S with 3-mercaptopyruvate as the donor of sulfur [31]. Further studies are required to investigate whether taurine differentially regulates H 2 S-producing enzyme expression for such reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The human 3MST enzyme is encoded by the MPST gene on the long arm of chromosome 22 in the subtelomeric region q13.1 [ 125 ]. The MPST gene is 5.6 kbp in length with only two exon regions [ 126 ].…”
Section: H 2 S Enzymatic Machinerymentioning
confidence: 99%
“…Mercaptopyruvatesulfurtransferase (3MST) belongs to the family of sulfurtransferases, which catalyze the transfer of a sulfur from a sulfur donor to a thiophilic acceptor by the formation of a protein cysteine persulfur intermediate [52]. The sulfur atom donor is 3-mercaptopyruvate, and the kinetically favored acceptor under physiological conditions is thioredoxin [53] (Figure 6).…”
Section: Figurementioning
confidence: 99%